Answer

Verified

473.7k+ views

Hint- Here, we will proceed with the help of factorization as well as discriminant formula to solve for the two roots of the given quadratic equation. For discriminant method we will apply the general formula $x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$ for any quadratic equation $a{x^2} + bx + c = 0$.

Complete step-by-step answer:

Given quadratic equation in variable x is ${x^2} + 7x + 12 = 0{\text{ }} \to {\text{(1)}}$

Here, we can solve this quadratic equation with the help of factorization method. The given quadratic equation can be written as

$ \Rightarrow {x^2} + 7x + 12 = 0 \Rightarrow {x^2} + 3x + 4x + 12 = 0 \Rightarrow x\left( {x + 3} \right) + 4\left( {x + 3} \right) = 0 \Rightarrow \left( {x + 3} \right)\left( {x + 4} \right) = 0$

Either $

\left( {x + 3} \right) = 0 \\

\Rightarrow x = - 3 \\

$ or $

\left( {x + 4} \right) = 0 \\

\Rightarrow x = - 4 \\

$

Hence, the two roots of the given quadratic equation are -3 and -4.

We can also solve the given quadratic equation by using the discriminant method.

For any general quadratic equation $a{x^2} + bx + c = 0{\text{ }} \to {\text{(2)}}$

According to discriminant method, the roots of this quadratic equation is given by

$x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}{\text{ }} \to {\text{(3)}}$

By comparing equations (1) and (2), we get

a=1, b=7 and c=12

Using the formula given by equation (3), the roots of the given quadratic equation are given by

\[x = \dfrac{{ - 7 \pm \sqrt {{{\left( 7 \right)}^2} - 4 \times 1 \times 12} }}{{2 \times 1}} = \dfrac{{ - 7 \pm \sqrt {49 - 48} }}{2} = \dfrac{{ - 7 \pm \sqrt 1 }}{2} = \dfrac{{ - 7 \pm 1}}{2}\]

Either \[x = \dfrac{{ - 7 + 1}}{2} = \dfrac{{ - 6}}{2} = - 3\] or \[x = \dfrac{{ - 7 - 1}}{2} = \dfrac{{ - 8}}{2} = - 4\]

So, the two roots of the given quadratic equation are -3 and -4.

Clearly, we are getting the same results from both factorization method and discriminant method.

Note- In these types of problems, we can use either factorization method or discriminant method to obtain the roots of the given quadratic equation. But discriminant method is usually adopted because it is an easier method as compared to factorization method for finding the roots of the given quadratic equation.

Complete step-by-step answer:

Given quadratic equation in variable x is ${x^2} + 7x + 12 = 0{\text{ }} \to {\text{(1)}}$

Here, we can solve this quadratic equation with the help of factorization method. The given quadratic equation can be written as

$ \Rightarrow {x^2} + 7x + 12 = 0 \Rightarrow {x^2} + 3x + 4x + 12 = 0 \Rightarrow x\left( {x + 3} \right) + 4\left( {x + 3} \right) = 0 \Rightarrow \left( {x + 3} \right)\left( {x + 4} \right) = 0$

Either $

\left( {x + 3} \right) = 0 \\

\Rightarrow x = - 3 \\

$ or $

\left( {x + 4} \right) = 0 \\

\Rightarrow x = - 4 \\

$

Hence, the two roots of the given quadratic equation are -3 and -4.

We can also solve the given quadratic equation by using the discriminant method.

For any general quadratic equation $a{x^2} + bx + c = 0{\text{ }} \to {\text{(2)}}$

According to discriminant method, the roots of this quadratic equation is given by

$x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}{\text{ }} \to {\text{(3)}}$

By comparing equations (1) and (2), we get

a=1, b=7 and c=12

Using the formula given by equation (3), the roots of the given quadratic equation are given by

\[x = \dfrac{{ - 7 \pm \sqrt {{{\left( 7 \right)}^2} - 4 \times 1 \times 12} }}{{2 \times 1}} = \dfrac{{ - 7 \pm \sqrt {49 - 48} }}{2} = \dfrac{{ - 7 \pm \sqrt 1 }}{2} = \dfrac{{ - 7 \pm 1}}{2}\]

Either \[x = \dfrac{{ - 7 + 1}}{2} = \dfrac{{ - 6}}{2} = - 3\] or \[x = \dfrac{{ - 7 - 1}}{2} = \dfrac{{ - 8}}{2} = - 4\]

So, the two roots of the given quadratic equation are -3 and -4.

Clearly, we are getting the same results from both factorization method and discriminant method.

Note- In these types of problems, we can use either factorization method or discriminant method to obtain the roots of the given quadratic equation. But discriminant method is usually adopted because it is an easier method as compared to factorization method for finding the roots of the given quadratic equation.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

At which age domestication of animals started A Neolithic class 11 social science CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Summary of the poem Where the Mind is Without Fear class 8 english CBSE

One cusec is equal to how many liters class 8 maths CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE